KEBIJAKAN PEMERINTAH DAERAH DALAM PENERAPAN MASYARAKAT EKONOMI ASEAN (MEA) TERHADAP SEKTOR KERAJINAN BATIK MELAYU RIAU TAHUN 2014-2015 - Kasih, Putri Tiara; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The 2020 acceleration of ASEAN Economic Community to be coming 2015 is one of the seriousness from the follow countries of ASEAN to realize the economic cooperation in Southeast Asia. Indonesia will be conforted the opportunity and defiance at once when the ASEAN free trade enfprced. To abuse the opportunity, Indonesia makes afforts in Micro, Small, and Medium Enterprises in Indonesia. Micro, Small and Medium Enterprises is one of important sector in Indonesia that have to empowered, because it gave significant contribution in Indonesia’s economic matter. Indonesia has prepare many various of program and wisdom to increase the Indonesia’s Micro, Small and Medium Enterprises and Small Medium Industry competitiveness to confront the ASEAN Economic Community 2015.This research, there are some things that can be concluded in the policies issued by the government in helping SMEs in particular to the craft of Batik Melayu Riau ; first, the creation of business climate, small and medium conducive to the performance indicators of the number of SMEs receiving facilities capital namely by members of training on ongoing basis, and the lend both bank and non-bank. The second, program is to improve the quality of institutional cooperation with the indicator increasing active cooperatives in the province of Riau. Namely to enable cooperatives in theregions so that the entrepreneurs were able to reach them. Thirdly the provincial government to help entrepreneurs to promote their product into and out of the country for example Malaysia, Singapore, Hongkong and others.Keyword : ASEAN Economic Community , Micro, Small, and Medium Enterprises , Batik Melayu Riau.